Pediatric Septic Arthritis of the Knee in Limited Health Facilities: A Case Report - Andariska, Ni Made Gita; Marthadani, Dandan (Jurnal KESANS : Kesehatan dan Sains, 2024)
Septic arthritis occurs when microbial agents infect a joint space, with the knee being one of the most affected areas. Failure to promptly diagnose or treat the condition can lead to permanent joint damage. In this report, we present the case of an eight-year-old boy who was hospitalized due to acute swelling in his right knee. This case highlights that relying solely on susceptibility testing to guide antibiotic therapy may not be sufficient in managing such conditions